Effect of Delayed Versus Immediate Umbilical Cord Clamping on Maternal Blood Loss in Term Cesarean Delivery: A Randomized Clinical Trial. Issue 3 (September 2020) - Purisch, S.E.; Ananth, C.V.; Arditi, B.; Mauney, L.; Ajemian, B.; Heiderich, A.; Leone, T.; Gyamfi-Bannerman, C.
Abstract : ( JAMA . 2019;322:1869–1876) In 2017, the American College of Obstetricians and Gynecologists recommended that providers delay umbilical cord clamping for at least 30 to 60 seconds after the birth of a preterm or term neonate, assuming that the neonate does not require resuscitation. While the literature strongly supports this recommendation as a neonatal benefit, studies on maternal outcomes are lacking. Furthermore, information regarding the impact of delayed umbilical cord clamping on the mother and neonate during cesarean delivery is also lacking. This study aimed to compare the impact of maternal blood loss when the umbilical cord was clamped immediately as compared with delayed during cesarean delivery.